2014
DOI: 10.1097/spc.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of people at the end of life

Abstract: Although the evidence of outcome studies is small, the research agenda is broadening to include nontraditional families and caregivers in low-and middle-income countries.The recent trial of psychoeducational interventions suggests that longer-term benefits are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It could be used internationally, although with some societal adaptions. Intervention studies with randomized designs based in theory have previously been found lacking in palliative care . Although the intervention is complex, incorporating several different components, its delivery is simple and demands few resources.…”
Section: Discussionmentioning
confidence: 99%
“…It could be used internationally, although with some societal adaptions. Intervention studies with randomized designs based in theory have previously been found lacking in palliative care . Although the intervention is complex, incorporating several different components, its delivery is simple and demands few resources.…”
Section: Discussionmentioning
confidence: 99%
“…Harding's study from 2014 defines informal caregivers as ''unpaid, informal providers of one or more physical, social, practical, or emotional tasks.'' 9 To be able to fulfill this demanding role, the caregivers need qualified support.…”
Section: Introductionmentioning
confidence: 99%
“…Swedish palliative home care teams are in charge of health-care issues, whereas the home help services provide assistance with the activities of daily living (washing, clothing, meals, etc). Harding’s study from 2014 defines informal caregivers as “unpaid, informal providers of one or more physical, social, practical, or emotional tasks.” 9 To be able to fulfill this demanding role, the caregivers need qualified support.…”
Section: Introductionmentioning
confidence: 99%